DEFB1 polymorphisms and HIV-1 mother-to-child transmission in Zambian population. - Zupin, Luisa; Polesello, Vania; Segat, Ludovica; Kamada, Anselmo Jiro; Kuhn, Louise; Crovella, Sergio (J Matern Fetal Neonatal Med, 2018)
INTRODUCTION: Human Beta Defensin-1 (hBD-1) is a component of the innate immune system, the first line of defence against pathogens, already reported as involved in the susceptibility to HIV-1 infection and HIV-1 mother-to-child transmission (MTCT) in different populations. We investigated the role of DEFB1 gene (encoding for hBD-1) functional polymorphisms in the susceptibility to HIV-1 MTCT in a population from Zambia. METHODS: Four selected polymorphisms within DEFB1 gene, three at the 5' untranslated region (UTR), namely -52G > A (rs1799946), -44C > G (rs1800972) and -20G > A (rs11362) and one in the 3'UTR, c.*87A > G (rs1800972), were genotyped in 101 HIV-1 positive mothers (26 transmitters -27% and 75 not transmitters -73%) and 331 infants born to HIV-1 infected mothers (85 HIV-1 positive -26% and 246 exposed but not infected -74%). RESULTS: DEFB1 c.*87-A allele was more frequent among HIV- children with respect to HIV+ (with intrauterine MTCT). Concerning DEFB1 haplotypes, GCGA haplotype resulted more represented in HIV- than HIV+ infants and DEFB1 ACGG haplotype presented increased frequency in HIV- children respect to HIV+ (with intra-partum MTCT) (p = .02, p = .002 and p = .006, respectively). CONCLUSIONS: DEFB1 polymorphisms were significantly associated with decreased risk of HIV-1 infection acquisition in the studied Zambian population suggesting that they may play a role in HIV-1 MTCT.